Mapping of Potential Groundwater Using Electrical Resistivity Imaging (ERI) at Low Land Area of Parit Raja Johor - Riwayat, Akhtar Izzaty; Ahmad Nazri, Mohd Ariff; Ahmad, Noor Aliza (International Journal of Integrated Engineering, 2022)
Electrical Resistivity Imaging (ERI) has emerged as an important technique in geophysical surveys for gaining more information and locating hidden water. This method was used at Parit Raja, Johor to investigate the location of underground water storage. Two-dimensional (2D) geoelectrical imaging has been used for this study. The imaging method was used at three different locations in the study area to identify potential aquifer and suitable locations for boreholes that would serve as observation wells. A Schlumberger array was set up during data acquisition since it can imagine deeper profile data and suitable for areas with a homogeneous layer. For 2D subsurface images, the raw data were processed with the RES2DINV software. According to the ERI results, this area was dominant with low resistivity values of less than 10 ?m and potential shallow aquifer depths ranging from 10 to 30 m. Furthermore, the chargeability value obtained from Induced Polarization (IP) supported this point. According to the IP data, the chargeability at that point was between 0 and 1 ms, indicating the presence of a groundwater in the study area.